Novel spectrofluorimetric method for boldine alkaloid determination in herbal drugs and phytopharmaceuticals - Peralta, Cecilia Mariana (2017)
A new green on-line method for Boldine determination (BOL) in herbal drugs andphytopharmaceuticals, using its native fluorescence in acid media (λex = 282 nm; λem = 373 nm) has been developed. The presented methodology involves for the first time, a flow injection (FI) strategy using a mini-column of multiwalled carbon nanotubes as retention agent coupled with molecular fluorescence. Different parameters influence as sample pH and flow rate, eluent flow rate and composition; on BOL sensitivity and elution time was investigated by multifactorial techniques.Adequate dynamic calibration range (r2 = 0.9993) was obtained over a concentrationinterval of 0.029 ? 27.0 µg mL−1 BOL. The limits of detection (LOD) and quantification (LOQ) were 0.008 and 0.029 µg mL−1 , respectively. The average recoveries in explored samples ranged from 95 % to 103 %. Under optimized conditions, the throughput sample as high as 30 h−1 was achieved with high repeatability performance (99 %). The proposed development represents a useful and valuable tool emulating the analytical efficiency of the official methodologies for quality control of herbal and phytopharmaceutical drugs containing BOL. Moreover, this approach shows advantages respect to low cost, simplicity and environmental and analyst friendly.